Industry Evolution: Diversity, Selection and the Role of Learning - D.B. Audretsch; P. Houweling; A.R. Thurik (Tinbergen Institute, 1998)
The purpose of this paper is to show how institutional and evolutionary economics provide better insights as to whysome firms survive and others do not than does neoclassical economics. At the heart of the evolutionary theory isthe view that new firms are a manifestation of diversity and that their subsequent survival is shaped by the selectionprocess. Despite immense institutional and historical differences across these different economic systems such asthose in North America, Japan and Europe, evolutionary economics explains the role that diversity, selection andlearning plays in economic development. We use a Dutch data set and a model on who survives and who doesn't toexplain this role.
Keywords: 330; Industrie; Evolutionsökonomik; Lernprozess; Theorie